Long‐Term Morphodynamics of a Coupled Shelf‐Shoreline System Forced by Waves and Tides, a Model Approach. Issue 12 (13th December 2021) - Nnafie, A.; de Swart, H. E.; Falqués, A.; Calvete, D.
Abstract: Sand ridges, with length scales of several km, are prominent features of the seafloor landscape of many sandy continental shelves. Knowledge about the extent to which these ridges influence the large‐scale (i.e., decadal and kilometer scales) morphodynamic evolution of the adjacent shoreline and vice versa (shelf‐shoreline morphodynamic coupling) is limited. The present work aims at quantifying this coupling by using a coupled nonlinear shelf‐shoreline model forced by tides and different wave conditions. Model results show that the presence of sand ridges on the shelf creates longshore non‐uniform wave patterns, which act as a forcing template for the morphodynamic development of the shoreline. The shelf‐shoreline coupling primarily works one way, meaning that the morphodynamic evolution of the shelf affects the evolution of the shoreline. When wave propagation is predominantly aligned with the long axis of the shelf ridges, the forced shoreline undulations are so prominent, that they affect the shelf morphology (significant two‐way coupling). Moreover, for those waves, the longshore spacing of the ridges is strongly imprinted on the shoreline morphology. Weaker shoreline undulations develop for waves that propagate more across the ridges and the weakest for time‐varying wave conditions with large variability in their angles of propagation. Model results compare fairly well with observations. Physical mechanisms underlying the different morphodynamic responses of the coupled shelf‐shoreline system to different wave conditions are also given. Plain Language Summary: Huge sand ridges (scales of 10 kilometers) are observed on the seafloor of many sandy continental shelves. Knowledge about the effects of these ridges on the evolution of the adjacent shoreline is limited. The present study addresses these effects using a coupled shelf‐shoreline model. Model results show that, when waves propagate along the sand ridges, the latter cause the development of large shoreline undulations, which have the same longshore spacing as the ridges. The shoreline undulations are weak for time‐varying wave conditions with large wave directionality (i.e., large variability in their wave angles). Wave climates with a large wave directionality, as is the case of the Belgium coast, are expected to have weak shoreline undulations compared with wave climates with a small wave directionality (e.g., wave climate of Fire Island) Key Points: Ridges on the shelf provide a forcing template for the large‐scale (decadal and kilometer scales) morphodynamic development of the shoreline When waves propagate along ridges, strong shoreline undulations develop, which feed back to the shelf morphology (two‐way coupling) For time‐varying waves with large variability in their angles of propagation, shoreline undulations are small